Facioscapulohumeral muscular dystrophy: new insights from compound heterozygotes and implication for prenatal genetic counselling. Issue 3 (3rd January 2012) - Scionti, Isabella; Fabbri, Greta; Fiorillo, Chiara; Ricci, Giulia; Greco, Francesca; D'Amico, Roberto; Termanini, Alberto; Vercelli, Liliana; Tomelleri, Giuliano; Cao, Michelangelo; Santoro, Lucio; Percesepe, Antonio; et al.
Abstract : Background: Facioscapulohumeral muscular dystrophy (FSHD) is considered an autosomal dominant disease with a prevalence of 1 in 20 000. Almost all patients with FSHD carry deletions of integral copies of tandem 3.3 kb repeats (D4Z4) located on chromosome 4q35. However, FSHD families have been reported in which individuals carrying a D4Z4-reduced allele remain asymptomatic. Recently, it has been proposed that the D4Z4-reduced allele is pathogenic only in association with the permissive haplotype, 4APAS. Methods and results: Through the Italian National Registry for FSHD (INRF), genotype–phenotype correlations were extensively studied in 11 non-consanguineous families in which two D4Z4-reduced alleles segregate. Overall, 68 subjects carrying D4Z4-reduced alleles were examined, including 15 compound heterozygotes. It was found that in four families the only FSHD-affected subject was the compound heterozygote for the D4Z4-reduced allele, and 52.6% of subjects carrying a single D4Z4-reduced 4A161PAS haplotype were non-penetrant carriers; moreover, the population frequency of the 4A161PAS haplotype associated with a D4Z4-reduced allele was found to be as high as 1.2%. Conclusions: This study reveals a high frequency of compound heterozygotes in the Italian population and the presence of D4Z4-reduced alleles with the 4A161PAS pathogenic haplotype in the majority of non-penetrant subjects in FSHD families with compound heterozygosity. These data suggest that carriers of FSHD-sized alleles with 4A161PAS haplotype are more common in the general population than expected on the basis of FSHD prevalence. These findings challenge the notion that FSHD is a fully penetrant autosomal dominant disorder uniquely associated with the 4A161PAS haplotype, with relevant repercussions for genetic counselling and prenatal diagnosis.